Establishment of the Normal Reference Range of Thrombelastogram among the Healthy Population and Pregnants in China - Rong GUI; Xueyuan HUANG; Ming ZHOU; Shujuan OUYANG; Yunfeng FU; Hao TANG; Fengxia LIU; Rong HUANG; Meng GAO; Hang DONG; Yongjun WANG (Tehran University of Medical Sciences, 2019)
Background: We aimed to establish the reference range of thrombelastogram (TEG) for Chinese healthy volunteers and pregnant women and analyze the influence factors. Methods: Blood samples were collected from healthy volunteers and pregnant women at five tertiary hospitals (the Third Xiangya Hospital of Central South University, the Second Xiangya Hospital of Central South University, Hunan Provincial People's Hospital, Hunan Cancer Hospital and Changsha Central Hospital) in 2016. The effects of age, gender, blood type, and full-term pregnancy on the reference range of normal TEG for healthy volunteers and pregnant women were studied. The specificity of TEG in detecting coagulation disorder. Results: For healthy volunteers, the normal ranges of TEG parameters were as follows: R, 4.3-9.3 min; K, 1.2-3.2 min; α, 50.2-71.2°; MA, 54.1-71.3 mm; LY30: 0%-2.2%; CI, -3.8-2.4. At least one parameter exceeded the normal range specified by the manufacturer in 20.3% of the healthy volunteers; about 7.6% healthy volunteers were diagnosed as coagulation disorder by the above standards; the specificity of detection was 79.7%. There were significant differences in R, K, α, MA and CI between males and females (P<0.01). For pregnant women, the normal ranges of TEG were as follows: R, 3.9-7.5 min; K, 1.0-2.4 min; α, 57.6-74.9°; MA, 55.7-75.7 mm; LY30, 0%-0.56%; CI, -0.97-3.6. Pregnant women having O blood group had a dramatically prolonged R. Full-term pregnancy had no significant impact on TEG results. Conclusion: Compared with pregnant women having non-O blood group, those having O blood group had a dramatically prolonged R and showed greater tendency to hemorrhage during and after parturition.